Zeolite Utilization as a Catalyst and Nutrient Adsorbent of an Organic Fertilizer Process From Palm Oil Mill Effluent as Raw Material - Ida Nursanti; Dedik Budianta; Adipati Napoleon; Yakup Parto (JOURNAL OF TROPICAL SOILS, 2013)
Palm Oil Mill Effluent (POME) cannot be directly used as an organic fertilizer source due to its high Biological Oxygen Demand (BOD) thus it is not  environmentally safely. To increase the high quality of organic fertilizer obtained, the liquid wastes are needed to be processed in order to decrease the BOD to degrade both the soluble and suspension materials of organic materials. The altenative process to be conducted to make a better quality of POME is by adding the adsorbent. The aim of the research was to study the effect of zeolite utilization and duration of hydrolysis process in order to increase the nutrients content and to decrease the BOD of POME. The research was conducted at  the PT Sumbertama Nusa Pertiwi Jambi, Indonesia in August 2012 until February 2013. The sample of POME was taken from the inlet of the factory’s  acidulating pool. There were several doses of zeolite  as treatments which were 0, 5, 10, 15% and several durations of hydrolysis process which were 1,2,3 and 4 weeks. Active zeolite was added to POME and then it was fermented with different hydrolysis duration times as mentioned above. The research showed that application of  zeolite  and  duration of hydrolysis process significantly affected the pH, N,  P, K, Al, Fe, BOD of  POME and the adsorption of  N, P, K, Al, Fe by zeolite. It can be concluded that 10% of zeolite incubated  in  two weeks duration of hydrolysis process produced higher nutrient of N, P, K  with BOD, Al, Fe and pH matched  with the waste quality standard. The highest efficiency of  N, P and K adsorbent was show by the 15% of zeolite  which was incubated for two weeks of hydrolysis process.Keyword: Hydrolysis process duration, nutrient content, palm oil mill effluent, zeolite.[How to Cite: Nursanti I, D Budianta, A Napoleon and Y Parto. 2013.Zeolite Utilization as a Catalyst and Nutrient Adsorbent of an Organic Fertilizer Process From Palm Oil Mill Effluent as Raw Material. JTrop Soils 18 (3): 177-184. Doi: 10.5400/jts.2013.18.3.177][Permalink/DOI: www.dx.doi.org/10.5400/jts.2013.18.3.177] REFERENCESAno AO and CI Ubochi. 2007. Neutralization of soil acidity by animal manures: mechanism of reaction. Afr J Biotechnol 6: 364-368.Budianta D. 2005. Potensi limbah cair pabrik kelapa sawit sebagai sumber hara untuk tanaman perkebunan. Dinamika Pert 20: 273-282 (in Indonesian).Djajadi B Helianto and N Hidayah. 2010. Pengaruh media tanam dan frekuensi pemberian air terhadap sifat fisik, kimia dan biologi tanah serta pertumbuhan jarak pagar. J Littri 16: 64-69 (in Indonesian).Dhayat NR. 2011. Bioremediasi lumpur minyak bumi dengan zeolit dan mikroorganisme serta pengujiannya terhadap tanaman sengon                                      (Paraserianthes falcataria).http://pustaka. unpad.ac.id/wp-content/uploads/2009/04/bioremediasi_lumpur_minyak_bumi_ dengan_zeolit_dan_mikroorganisme.pdf       (accessed on 23   December 2011).Ersoy B and MS Celik. 2003. Effect of hydrocarbon chain length on adsorption of cationic onto clinoptilolite. Clay Clay Miner 51: 173-181.Fungaro DA. 2002. Removal of toxic metals from waters using zeolites from coal. J Environ Qual 2: 116-120.Feuerstein M, RJ Accardi and RF Lobo. 2000. Adsorption of nitrogen and oxygen in the zeolit. J Phys Chem 104: 1082-1087.Gu Z, F Buyuksonmez, S Gajaraj and N Edward. 2011. Adsorption of phosphate by goethite and zeolite: effects of humic substances from green waste compost. ProQuest Agric J  19 : 197-204.Jabri A. 2008. Kajian metode penetapan kapasitas tukar kation zeolit sebagai pembenah tanah untuk lahan pertanian terdegradasi. Jurnal Standardisasi. 10(2): 56-69 (in Indonesian).Karamah EF, Syafrizal and  AN Sari. 2010. Pengolahan limbah campuran logam Fe, Cu, Ni dan ammonia menggunakan metode flotasi-filtrasi dengan zeolit alam Lampung sebagai bahan pengikat. Proseding Seminar Nasional Teknik Kimia Lembaga Penelitian UGM. 26 Januari 2010.Yogyakarta (in Indonesian).Kundari NA,  A Susanto and MC Prihatiningsih. 2010. Adsorpsi Fe dan Mn dalam limbah cair dengan zeolit alam. Seminar Nasional VI Sdm Teknologi Nuklir Yogyakarta, 18 November 2010 (in Indonesian). Li Z, D Allesi and L Allen. 2000. Influence of quartenary ammonium of sorption of selected metal cations onto clinoptilolite zeolite. J Environ Qual 31: 1106-1114.Luturkey YA, A Ahmad and SZ Amraini. 2010. Uji kinerja bioreaktor hibrid anaerob bermedia tandan kosong dan pelepah sawit dalam penyisihan COD limbah cair pabrik minyak sawit. Prosiding Seminar Teknik Kimia. ITB, Bandung (in Indonesian).Ma AN. 2000. Environmental Management for the Oil Palm Industry. Palm Oil Dev 30: 1- 10.Oste LA, TM Lexmond and V Riemsdijk. 2002. Metal immobilization in soils using synthetic zeolites. J Environ Qual 31: 813-821.Raharjo PN. 2009. Studi banding teknologi pengolahan limbah cair pabrik kelapa sawit. J Teknol Lingk 10: 9-18 (in Indonesian).Raharjo PN. 2006. Teknologi pengelolaan limbah cair yang ideal untuk pabrik kelapa sawit. J Agr Indon 2 : 66-72 (in Indonesian).Simanjuntak H. 2009.  Studi korelasi antara BOD dengan unsur hara N, P dan K dari Limbah Cair Pabrik Kelapa Sawit [Thesis]. Sekolah Pascasarjana Universitas Sumatera Utara Medan (in Indonesian).Sumarlin LO, S Muharam and A Vitaria. 2008. Pemerangkapan ammonium (NH4+) dari urine dengan zeolit pada berbagai variasi konsentrasi urine. J Valensi 1: 110-117 (in Indonesian).Susanti PD and S Panjaitan. 2010. Manfaat zeolit dan rock phosphat dalam pengemposan limbah pasar. Prosiding Standardisasi 4 Agustus 2010. Banjarmasin (in Indonesian).Vaulina E. 2002. Potensi zeolit alam sebagai absorban logam-logam berat pada limbah perairan. Majalah Ilmiah  2: 1-8 (in Indonesian).Waluyo L. 2009. Mikrobiologi Lingkungan. Edisi 2. UMM Press. Malang. 341 p. (in Indonesian).